2019
DOI: 10.1103/physrevlett.122.015003
|View full text |Cite
|
Sign up to set email alerts
|

Thermionic Cooling of the Target Plasma to a Sub-eV Temperature

Abstract: Contemporary models of bounded plasmas assume that the target plasma electron temperature far exceeds the temperature of the cold electrons emitted from the target, Temit. We show that when the sheath facing a collisional plasma becomes inverted, the target plasma electron temperature has to equal Temit even if the upstream plasma is hotter by orders of magnitude. This extreme cooling effect can alter the plasma properties and the heat transmission to thermionically emitting surfaces in many applications. It a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
24
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(25 citation statements)
references
References 37 publications
0
24
1
Order By: Relevance
“…Here, we show the first results of UEDGE modeling of a plasma equilibrium under conditions emulating both the "standard" (or previously accepted, "traditional" sheath model) and inverse sheath at the plasma edge. While plasma dynamics shown in kinetic simulations indicate the possibility of an improved transition to detachment via the inverse sheath regime [3] , such favorable results are not seen in our simulations. In this paper, we will present and discuss our plasma model and results for "standard" and "inverse" sheath regimes.…”
Section: Introductioncontrasting
confidence: 65%
See 2 more Smart Citations
“…Here, we show the first results of UEDGE modeling of a plasma equilibrium under conditions emulating both the "standard" (or previously accepted, "traditional" sheath model) and inverse sheath at the plasma edge. While plasma dynamics shown in kinetic simulations indicate the possibility of an improved transition to detachment via the inverse sheath regime [3] , such favorable results are not seen in our simulations. In this paper, we will present and discuss our plasma model and results for "standard" and "inverse" sheath regimes.…”
Section: Introductioncontrasting
confidence: 65%
“…Strong electron thermionic emission from material surfaces has been proposed to cause the formation of an "inverse sheath", a regime at the plasma edge where electron emission (in conjunction with ion and electron cooling due to charge exchange and other collisions) prevents the flow of cold ions to the surface [1][2][3] . This inverse sheath (different than the space-charge limited sheath) features a monotonic, positive potential at the material surface that forms when the emission of electrons from the surface exceeds the influx of electrons from the plasma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This approach, that is, choosing a significant breakdown of charge neutrality, was originally adopted by Tonks and Langmuir, while recent study of Chabert confirmed that such choice makes DC sheath size nearly independent of plasma properties, thus facilitating comparison under various conditions. A value of δse = 1% was chosen in Campanell's recent work . The influence of such choice on sheath size is shown in Figure .…”
Section: Theoretical Modeling Of Emissive Rf Sheathmentioning
confidence: 99%
“…Sinusoidal source is fixed as Dirichlet-type condition at boundaries. Adopted simulation parameters are listed below to help replicate simulation results: source frequency 13.56 MHz, bulk plasma density 0 = 5 × 10 14 The simulation produces noise-free data for better understanding of sheath physics, similar methods were used in several previous works related to plasma sheath [28][29][30][31] . More detailed algorithm was shown in our previous works of bounded plasma 15,32 .…”
mentioning
confidence: 99%